2022
DOI: 10.3390/agriculture12050658
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Regulation and Osmotic Adjustment in Sorghum in Response to Salinity

Abstract: Sorghum bicolor (L.) Moench, one of the most important dryland cereal crops, is moderately tolerant of soil salinity, a rapidly increasing agricultural problem due to inappropriate irrigation management and salt water intrusion into crop lands as a result of climate change. The mechanisms for sorghum’s tolerance of high soil salinity have not been elucidated. This study tested whether sorghum plants adapt to salinity stress via stomatal regulation or osmotic adjustment. Sorghum plants were treated with one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…indicator of photosynthetic function (Xu et al, 2008;Dourado et al, 2022). It has been found that the chlorophyll level of plants decreases with aggravated salt stress (Pires et al, 2015;Rachoski et al, 2015;Dabrowski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…indicator of photosynthetic function (Xu et al, 2008;Dourado et al, 2022). It has been found that the chlorophyll level of plants decreases with aggravated salt stress (Pires et al, 2015;Rachoski et al, 2015;Dabrowski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Nxele found that salinity stress could reduce water retention in sorghum plants ( Nxele et al., 2017 ), which is a common response to salt stress. Under adverse circumstances, the chlorophyll level in the plant is a good indicator of photosynthetic function ( Xu et al., 2008 ; Dourado et al., 2022 ). It has been found that the chlorophyll level of plants decreases with aggravated salt stress ( Pires et al., 2015 ; Rachoski et al., 2015 ; Dąbrowski et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on salt tolerance mechanisms in sorghum revealed that 84 differentially expressed genes ( DEGs ) are associated with photosynthesis in salt-tolerant crops after salt stress. During stomatal regulation and osmotic adjustment in sorghum in response to salinity [ 93 ], up to 51 genes are related to chlorophyll synthesis; most DEGs are related to chlorophyll, PS II, and cytochrome, and all the DEGs related to ATP synthase and carbon fixation are upregulated [ 95 ]. This suggests that salt stress can induce photosynthetic response genes in crops, and these genes related to photosynthetic electron transport may be activated by strong light energy conversion [ 96 ].…”
Section: The Molecular Mechanisms Of Sorghum Under Salt Stressmentioning
confidence: 99%
“…The response time of stomata during the critical period is very important in the survival of plants during drought and salinity stress, the quicker the plants respond, the better position they are in avoiding stress effects. This has been associated with the ability to withstand drought in phaseolus ( Markhart, 1985 ) cowpea ( Laffray and Louguet, 1990 ), sorghum ( Tsuji et al., 2013 ), soybean ( Hossain et al., 2015 ) and woody species ( Yan et al., 2017 ); salinity in maize ( Neto et al., 2004 ), Cotton ( Janagoudar, 2007 ), sorghum ( Duarado et al., 2022 ), Eruca sativa ( Hniličková et al., 2017 ). This was attributed to stomatal closure as a form of salinity stress coping mechanism.…”
Section: Morpho-physiological Responses To Environmental Stressmentioning
confidence: 99%